Ginga‐NCL architecture for plug‐ins. (31st July 2012) - Soares, Luiz Fernando G.; Moreno, Marcio F.; Marinho, Rafael S.; Bishop, Judith; Notkin, David
SUMMARY Ginga is the middleware of the Japanese‐Brazilian terrestrial digital TV (DTV) system, ISDB‐T B, and also the ITU Telecommunication Standardization Sector (ITU‐T) Recommendation for Internet Protocol television services. Ginga supports NCL (Nested Context Language) applications in its declarative environment (Ginga‐NCL) for which we devise an architecture for plug‐in integration. This paper focuses on this plug‐in architecture and its innovative solutions, detailing the plug‐in API, life‐cycle and control model, besides discussing how the architecture can be extended to other software systems, in particular to other DTV middleware systems. In the paper, we show how Ginga‐NCL can embed other declarative language engines. On the other hand, we also extend an HTML browser to allow it to embed Ginga‐NCL. This proof‐of‐ concept is important because NCL and HTML players are not only the most common players found in DTV middleware systems but also because they are ITU Telecommunication Standardization Sector Recommendations for terrestrial and Internet Protocol television services (NCL and Broadcast Markup Language (BML)/Lightweight Interactive Multimedia Environment (LIME)). Therefore, this proof‐of‐concept also provides a contribution to DTV middleware interoperability. Copyright © 2012 John Wiley & Sons, Ltd.